A simple algorithm for selecting cases to investigate acute and early HIV infections in low- and middle-income countries - Matsuda, Elaine Monteiro; Ahagon, Cintia Mayumi; Coelho, Luana Portes Ozório; Campos, Ivana Barros; Colpas, Daniela Rodrigues; Campos, Norberto Camilo; López-Lopes, Giselle Ibete Silva; Silva, Valeria Oliveira; de Oliveira, Isabela Penteriche [UNESP]; Brígido, Luís Fernando de Macedo (Wiley, 2022)
We documented the outcome of an over 10-year (2011–2021) effort to diagnose acute and early HIV infections (AEHI) in an Infectious Diseases Outpatient Clinic with limited resources. Of a total of 132, 119 HIV-RNA tests were performed from 2017 to 2020, 12 cases were identified, using a simple algorithm: risk exposure of 6 weeks or less before the visit and/or symptoms compatible with acute retroviral syndrome 7–30 days after exposure and/or undetermined 3rd generation rapid diagnostic test or serology. AEHI diagnoses varied from 2.4% among asymptomatic to 25% for undetermined serology cases using this simple screening applicable to different settings.
Keywords: acute HIV infection; diagnosis; HIV-1; rapid diagnostic test; viral load